Silent scream: revelations of teen-age pregnant students of their lived experience and testimonies - Correos, Arturo L. Jr. (Parañaque City: Olivarez College, 2019)
This case study endeavors to determine the lived experiences of early pregnancy among teen-age students in terms of the causes, effects, challenges and their coping mechanisms. The naturalistic model was used in the study with the purposively chosen informants with varied tools to cross-check their responses. Results show that curiosity, lack of sexual knowledge, financial and family problems and uncontrolled emotions cause pregnancy among teenagers. Teenage mothers face a lot of challenges after pregnancy like providing proper care and needs of their child. Teenage mothers have less possibility to finish their studies after engaging in early pregnancy. Taking care of the baby and providing financial assistance are challenges they encountered and tried to cope up with. The academic performance, the financial status and support of the family of teenage mothers determine if they can pursue their studies and achieve their dreams in life. Sex and sexuality education should not just be a concept but should be developed further as a complete discipline and much more research should be conducted to that regard.
Master Thesis
Keywords: Teenage mothers